Figur Intelektual Muslim dalam Qurâ€™an: Tafsir Tematik Terhadap Kata Ulul Albab - Amda, Ahmad Dibul (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
The main issues addressed in this study are the meaning and nature of the word Ulul Albab in the Qurâ€™an. In general, some theories say that Ulul Albab means a person who has intelligent thoughts, conscious heart, who is opened and understand the essence beyond the physical nature. The word also refers to one who enjoys what he sees and knows, and who always remembers Allah The Almighty through all things he sees and touches. Those meaningsare similar to the meaning of the term â€œIntellectualâ€ in the general senseknown bynowadays people. So, can the term Ulul Albab be translated into â€œIntellectual Muslimâ€?, and how is then the Qurâ€™anic conception of Ulul Albabâ€™s existences and characteristics?Thus, this study deals with the meanings and essence of Ulul Albab in the Qurâ€™an, the characteristics of Ulul Albab, and how to build Ulul Albab characteristics properly? This is a library research. The data analysis used content analysis on the material object in the form of verses of the Qurâ€™an by using Thematic Interpretation Method approach Ø§Ù„Ù€ØªÙ€ÙÙ€Ù€Ø³Ù€Ù€ÙŠÙ€Ù€Ø±Ø§Ù„Ù…Ù€Ù€ÙˆØ¶Ù€Ù€ÙˆØ¹Ù€Ù‰))Â (al-Tafsir al-Maudhuâ€™i) as a formal object, and supported by some relevant theories. The objective of this research is to find out the valid and concrete data or theories about the meanings and nature of Ulul Albab Â in the Qurâ€™an. This research results in several conclusions that; the term Ulul Albab in the Qurâ€™an has the same meaning as the term â€œIntellectual Muslimâ€, Al-Qurâ€™an describes several characteristics of Ulul Albab and how to build and developed the mentioned characteristics